The Impact of Financial Literacy and Entrepreneurial Mindset on Startup Growth in India - Ajay Shankar (Journal of Business Innovation and Accounting Research, 2025)
The Indian startup ecosystem has emerged as the third largest globally, with over 90,000 registered startups and more than 100 unicorns as of 2024. However, despite this remarkable growth, a significant proportion of startups fail within their first five years of operation, with financial risks and inadequate entrepreneurial capabilities being among the primary causes. This study investigates the impact of financial literacy and entrepreneurial mindset on startup growth in India, examining how these factors influence business sustainability, financial decision-making, and overall entrepreneurial performance. Employing a mixed-method research approach, this study synthesizes quantitative data from surveys administered to startup founders and qualitative insights from policy analysis and secondary sources. The findings reveal that financial literacy significantly reduces initial financial burdens, enhances cash-flow management, and improves the ability of Indian startups to attract investment. Furthermore, an entrepreneurial mindset characterized by innovation, adaptability, and financial discipline emerges as a critical determinant of startup survival and growth. The study contributes to the existing literature by providing empirical evidence on the synergistic relationship between financial knowledge and entrepreneurial orientation in the context of India's unique startup ecosystem, while offering policy recommendations for fostering sustainable entrepreneurial growth.